PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU ( STUDI PADA MAN 1 POLEWALI MANDAR) - Sapri Sapri; Sappeami Sappeami; Berlian Berlian (ILIN Institute, 2022)
This study aims to determine the principal's leadership style and the influence of the principal's leadership style on teacher performance. This research was conducted at MAN 1 Polewali Mandar. The population in this study were all 69 teachers at MAN 1 Polewali Mandar. The number of samples used was 69 people using Sugiyono's saturated sampling theory. Data collection was carried out by providing questionnaires, interviews and documentation. The analysis technique used in this study is descriptive statistics and inferential statistics using SPSS Version 23. The results of the study show that the leadership of the principal of MAN 1 Polewali Mandar belongs to a charismatic leadership style. The results of the analysis show that the principal's leadership style has a positive and significant effect on teacher performance at MAN 1 Polewali Mandar